Impact Of Prepregnancy Overweight And Obesity On Treatment Modality And Pregnancy Outcome In Women With Gestational Diabetes Mellitus - Linder, Tina; Eder, Anna; Monod, Cécile; Rosicky, Ingo; Eppel, Daniel; Redling, Katharina; Geissler, Franziska; Huhn, Evelyn A.; Hösli, Irene; Göbl, Christian S. (Frontiers in Endocrinology, 2022)
Background: We aim to evaluate the impact of prepregnancy overweight on treatment modalities of Gestational Diabetes Mellitus (GDM). We assessed the association of increased pregravid Body Mass Index (BMI) with dosing of basal and rapid acting insulin as well as pregnancy outcome. Methods: We included 509 gestational diabetic women (normal weight: 201, overweight: 157, obese: 151), attending the pregnancy outpatient clinic at the Department of Obstetrics and Gynecology, Medical University of Vienna, in this retrospective study. We used a prospectively compiled database to assess patient characteristics, treatment approaches – particularly maximum doses of basal and rapid acting insulin or metformin – and pregnancy outcome. Results: Increased BMI was associated with the need of glucose lowering medication (odds ratio (OR): 1.08 for the increase of 1 kg/m² BMI, 95%CI 1.05–1.11, p<0.001). Mothers with pregestational obesity received the highest amount of insulin. Metformin was more often used in patients with obesity who also required higher daily doses. Maternal BMI was associated with increased risk of cesarean section (OR 1.04, 95%CI 1.01–1.07, p<0.001) and delivering large for gestational age offspring (OR 1.09, 95%CI 1.04–1.13, p<0.001). Birthweight percentiles were highest in patients with obesity who required glucose lowering therapy. Conclusions: Treatment modalities and outcome in GDM pregnancies are closely related to the extent of maternal BMI. Patients with obesity required glucose lowering medication more often and were at higher risk of adverse pregnancy outcomes. It is crucial to further explore the underlying pathophysiologic mechanisms to optimize clinical management and individual treatment approaches.